Protective Effect of Baicalin Against Carbon Tetrachloride-Induced Acute Hepatic Injury in Mice - Sang-Won Park; Chan-Ho Lee; Yeong Shik Kim; Sam Sik Kang; Su Jin Jeon; Kun Ho Son; Sun-Mee Lee (Elsevier, 2008)
This study examined the effects of baicalin, a bioactive flavonoid isolated from Scutellariae Radix, on carbon tetrachloride (CCl4)-induced liver injury. Mice were treated intraperitoneally with 0.5 ml/kg CCl4and different groups of animals received 25, 50, 100, and 200 mg/kg baicalin. At 24 h after the CCl4treatment, the level of serum aminotransferases and lipid peroxidation was significantly elevated, whereas the hepatic glutathione content was decreased. These changes were attenuated by baicalin. The histological studies showed that baicalin inhibited the portal inflammation, centrizonal necrosis, and Kupffer cell hyperplasia, which are the three most common characteristics of CCl4-induced liver damage. The serum level and mRNA expression of tumor necrosis factor-α were markedly increased by the CCl4treatment but suppressed by baicalin. The mRNA and protein expression levels of inducible nitric oxide synthase and heme oxygenase-1 increased significantly at 24 h after the CCl4treatment. Baicalin attenuated the increase in the protein and gene expression of inducible nitric oxide synthase but augmented the increase in those of heme oxygenase-1. These findings suggest that baicalin protects hepatocytes from the oxidative damage caused by CCl4, and this protection is likely due to the induction of HO-1 expression and the inhibition of the proinflammatory mediators. Keywords:: baicalin, carbon tetrachloride (CCl4), heme oxygenase-1, oxidative stress, xyhproinflammatory mediator